Genetic variability and population structure analysis of Protostrongylus oryctolagi (Nematoda: Protostrongylidae) in Lepus europaeus from Central and Northern Italy - Ilaria Guarniero; Laura Stancampiano; Rafaella Franch; Elisa Armaroli; Fabio Macchioni; Enrico Negrisolo (PLoS ONE, 2025)
Nematodes are abundant and ubiquitous animals which are poorly known at intraspecific level. This work represents the first attempt to fill the gap on basic knowledge of genetic variability and differentiation in Protostrongylus oryctolagi, a nematode parasite of lagomorphs. 68 cox1 sequences were obtained from brown hares collected in five locations in Northern and Central Italy, highlighting the presence of a high amount of genetic variation inside this species. The eleven haplotypes identified (Haplotype diversity equal to 0.702) were split into two lineages: lineage A (comprising six different haplotypes, A1-A6) and lineage B (B1-B5). The mean intra-lineage amount of genetic variation was 0.3%, whereas the inter-lineage percentage of variation was ten-fold higher (3%). These two lineages were non-randomly distributed in the investigated areas. Lineage A showed a preference for Central Italy (Tuscany) even if it was sporadically found also in northern territories (Emilia-Romagna), while B-haplotypes were present exclusively in Emilia-Romagna. The analysis of molecular variance identified two main barriers to gene flow: (i) a strong major one which separate samples of Central Italy (PIA and GR7) from the northern ones (RE1, RE3 and MO1; ΦST = 0.750, P = 0.00); (ii) a secondary faint barrier which separates Pianosa island from Grosseto (ΦST = 0.133, P = 0.00). Any difference was found among northern samples (ΦST = 0.009, P = 0.00). The observed data may be explained by several factors ranging from the parasite’s biology (presence of a narrow host spectrum), the final host’s behaviour (small home range), the natural dispersion of the host-parasite dyad occurred in past or the recent passive men-mediated migration. Finally, the presence of unconventional shortened amplicons revealed the presence of NUMTs (nuclear copy of mitochondrial genes) in the P. oryctolagi nuclear genome, suggesting caution when using DNA barcode as unique marker for the identification of species belonging to this genus. “In short, if all the matter in the universe except the nematodes were swept away, our world would still be dimly recognizable”. Nathan Augustus Cobb, from "Nematodes and Their Relationships", 1915